Women in governance in South Asia - Omvedt, Gail (2005)
Even though south Asia claims some of the most powerful women leaders of the world, the overall political participation by women remains dismal. The obstacles to women's equal participation in governance in these countries are embedded in socio-cultural patterns of living and the intensely competitive nature of politics. This article examines various women empowerment initiatives like community management, local governance and reservations. It also analyses the representation of women in parliaments of these countries and suggests that what is needed is not a retreat from demanding quotas, but a consideration of the most useful forms of such reservations. Also with this, women's representation in the bureaucracy and in the structures of political parties also has to be increased. - Reproduced.
Keywords: Public administration - South Asia; Women in politics - South Asia; Women in politics